Pleth variability index measured in the sitting position before anesthesia can predict spinal anesthesia-induced hypotension in cesarean section: An observational study - Erhan Ozyurt (Journal of Obstetric Anaesthesia and Critical Care, 2022)
Background: Hypotension induced by spinal anaesthesia during caesarean section can have devastating effects on the parturient and foetus. This study investigated the ability to predict spinal anaesthesia-induced hypotension via the perfusion index and pleth variability index in the sitting position caesarean section. Materials and Methods: We enrolled 46 patients undergoing elective caesarean section in this study and used standard anaesthetic management in all patients. The haemodynamic parameters, perfusion index and pleth variability index of the patients were recorded at specific time points. Results: Hypotension occurred in 61.4% of the patients. There was a difference in the pleth variability index values between patients with and without hypotension at baseline as well as in the sitting position and after spinal anaesthesia (P = 0.023, 0.001, and 0.040, respectively). According to the receiver operating characteristic curve analysis, the pleth variability index value of the patients in the sitting position was a predictor of spinal anaesthesia-induced hypotension (area under the curve = 0.780, 95% confidence interval [CI]: 0.633–0.927, P = 0.001). The cut-off value of the pleth variability index (in the sitting position) for predicting hypotension was 20.5% (sensitivity: 76.5%, specificity: 70.4%). Multivariate logistic regression analysis revealed that an increased pleth variability index in the sitting position before spinal anaesthesia was an independent risk factor of spinal anaesthesia-induced hypotension (odds ratio: 0.78, 95% CI: 0.62–0.98, P = 0.034). Conclusion: The pleth variability index in the sitting position before spinal anaesthesia is a useful tool for predicting spinal anaesthesia-induced hypotension during caesarean section.